Reflections on the function and form of spending free time in the era of information technology and social media - Ilona Żeber-Dzikowska; Beata Cieśleńska; Jarosław Chmielewski (Edukacja Ustawiczna Dorosłych)
Leisure time plays a very important role in human life. It is usually associated with rest, but people depending on various factors e.g. age, habits, pressures of the environment, use it in different ways. Unfortunately, the forms of leisure are not always optimal for our mental and physical health. Every person is different, so his expectations for the forms of rest he does are different, but the most important thing is that after him a person feels physically and mentally better